Tolerability, pharmacokinetics and pharmacodynamics of CMAB001, an anti-CD11a antibody, in Chinese healthy volunteers and psoriatic patients - Li Xian-ping; Li Jing; Yan Heng; Zhou Bo; Li Bo-hua; Qian Wei-zhu; Hou Sheng; Wang Hao; Hao Fei; Guo Ya-jun (Acta Pharmacologica Sinica; Vol 33, No 8 (August 2012): Acta Pharmacologica Sinica, 2016)
Aim: To evaluate the pharmacokinetics (PK), pharmacodynamics (PD) and primary tolerability of an anti-CD11a monoclonal antibody (CMAB001) in Chinese healthy volunteers and psoriatic patients. Methods: Two open-label studies were conducted. One was a parallel-group, single-center, dose-escalation test, including 24 healthy adult volunteers from 18 to 45 years in age. All subjects randomly received a single subcutaneous injection dose of 0.5, 1.0 or 2.0 mg/kg. The other was a multiple-dose study: 10 adult psoriatic patients were administered weekly subcutaneous injections of 1.0 mg/kg for 7 weeks. Results: CMAB001 was well tolerated in the single- and multiple-dose studies. Slow absorption was observed in both studies. In the single-dose study, the concentration of CMAB001 reached its highest level 2 d later after the injection, and the Cmax increased in an approximate dose-proportionate manner, while the area under curve (AUC) showed much greater than dose-proportionate increase. In the multiple-dose study, the steady-state serum concentration level was attained following the 4th injection. Conclusion: CMAB001 exhibited a nonlinear pharmacokinetic profile over the dose range from 0.5 to 2.0 mg/kg, and was well tolerated in healthy volunteers and psoriatic patients.